Elimination of Oxidation‐Induced Stacking Faults in Silicon Single Crystals Using the Kyropoulos Crystal Growth Method. Issue 17 (14th April 2018) - Nouri, Ahmed; Chichignoud, Guy; Albaric, Mickael; Brize, Virginie; Zaidat, Kader
Abstract : Oxidation‐induced stacking faults (OSF rings) is a detrimental recurrent defect that appears along the silicon monocrystalline ingot obtained by Czochralski method. Most of the prior studies, related to Czochralski, focus on the increase of pulling rate to reduce this defect; the present work puts forward the low thermal gradient as an efficient parameter to avoid its formation. A modified Kyropoulos configuration is used to grow silicon crystals at low thermal gradient. Experiment shows that even a low pull‐up velocity, slower than the growth rate, is sufficient to completely eliminate this defect. The top part of the crystal, grown without any pull up has OSF rings. On the other hand, the parts of the crystal obtained with considerably low pull‐up velocity, in order to keep the growth below the free surface of the melt, do not have OSF rings. Even at low pull‐up velocity, the OSF defect can be avoided thanks to the controlled low thermal gradient in the crystal. Abstract : The low thermal gradient during crystal growth of silicon using Kyropoulos technique enhances the quality of the final silicon crystal. The decrease of thermal gradient suppresses efficiently the formation of oxidation‐induced stacking faults even at very low growth velocity.